2007
DOI: 10.3748/wjg.v13.i43.5699
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and pathological mechanism on magnetic resonance diffusion-weighted imaging after chemoembolization in rabbit liver VX-2 tumor model

Abstract: AIM:To investigate dynamic characteristics and pathological mechanism of signal in rabbit VX-2 tumor model on diffusion-weighted imaging (DWI) after chemoembolization. METHODS:Forty New Zealand rabbits were included in the study and forty-seven rabbit VX-2 tumor models were raised by implanting directly and intrahepatically after abdominal cavity opened. Forty VX-2 tumor models from them were divided into four groups. DWI was performed periodically and respectively for each group after chemoembolization. All V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Cysts can be distinguished from solid lesions easily. The cut-off ADC was reported to be approximately 2.5 × 10 -3 mm 2 /s for distinguishing cysts from other solid liver tumors[70]. Hemangioma is also relatively easy to distinguish from malignant lesions.…”
Section: Detection and Characterization Of Liver Tumorsmentioning
confidence: 99%
“…Cysts can be distinguished from solid lesions easily. The cut-off ADC was reported to be approximately 2.5 × 10 -3 mm 2 /s for distinguishing cysts from other solid liver tumors[70]. Hemangioma is also relatively easy to distinguish from malignant lesions.…”
Section: Detection and Characterization Of Liver Tumorsmentioning
confidence: 99%
“…Diffusion MR is currently a key area of clinical research due to its proposed ability to characterize properties such as cellularity in tumor (1–6) and normal tissues (7), architecture of the interstitium (8, 9), tumor histological type (10), and to elucidate tissue structure (for example, mapping the paths of white matter fibers in the brain (11)). In cancer, the apparent diffusion coefficient (ADC) is of particular interest due to observations of its reduced value in tumors relative to surrounding, radiologically normal tissues (12–21), its ability to detect and characterize regional necrosis (22–26), and increases in ADC resulting from successful response to treatment of cancer (27–37).…”
mentioning
confidence: 99%
“…The usefulness of DWI in the evaluation of therapeutic efficacy after TACE for hepatic tumors has already been reported in some animal and human studies. Some researchers have reported that areas of dead cells in VX-2 tumors in rabbits display high ADC, while areas of viable cells show low ADC after TACE (30,31). ADC values also correlated with pathological percentage of necrosis after TACE in a human study (32).…”
Section: Discussionmentioning
confidence: 92%